Przeżywanie ojcostwa w nauczaniu bł. Jana Pawła II - Kunka, Sławomir (Verbum Vitae, 2011)
The article picks up the theme of fatherhood in the teaching of John Paul II. The basic ideas of the teaching are to be sought in the publications by K. Wojtyla like ReflectionsonFatherhood and Radiation of Fatherhood. The issue of fatherhood is important for every human being, it lays at the foundations of our identity. The one who believes in God is aware of “being begotten” (cf. Ps 2:7; Acts 13:33) and of coming from God. God the Father is a source of every fatherhood (cf. Eph 3:15). One cannot be a father without being a child (cf. Matt 18:3), and to be a child means to acknowledge the Father and to become his son/daughter. Christ revealed God as his Father, he spoke of Him “my Father”, he taught his disciples the prayer of “Our Father” (cf. Matt 6:8-9; Rom 8:15). The only begotten Son of God, as the second Adam, restores the fatherhood of God to man. This way he makes the “solitude” of Adam shine with the “radiation of fatherhood”.